2018
DOI: 10.1002/jrs.5444
|View full text |Cite
|
Sign up to set email alerts
|

SERS and DFT study of 5F‐PB‐22

Abstract: In this work, a joint experimental and theoretical study on the synthetic cannabinoid, 5F-PB-22 (1-(5-fluoropentyl)-8-quinolinyl ester-1H-indole-3-carboxylic acid) is reported. The molecular vibrations of 5F-PB-22 were investigated by Raman and surface-enhanced Raman spectroscopy (SERS) spectroscopies. In parallel, quantum chemical calculations based on density functional theory (DFT) with the hybrid B3LYP exchange-correlation functional coupled with the standard 3-21G basis set were used to determine the geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Alkaseem and Baron reported a joint experimental and theoretical study on the synthetic cannabinoid, 5F‐PB‐22 (1‐(5‐fluoropentyl)‐8‐quinolinyl ester‐1H‐indole‐3‐carboxylic acid). They found that 5F‐PB‐22 was easily detected at 2 × 10 −8 M. Based on a predicted molecular adsorption geometry from the calculated electrostatic potential and the SERS spectrum, it is proposed that the quinoline moiety of the molecule lies in a preponderant parallel orientation to the silver surface with the plane of the indole ring being perpendicular to the surface . Atanasov et al carried out a SERS analyses of thiamethoxam assisted by Ag films and nanostructures that were produced by laser techniques.…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Alkaseem and Baron reported a joint experimental and theoretical study on the synthetic cannabinoid, 5F‐PB‐22 (1‐(5‐fluoropentyl)‐8‐quinolinyl ester‐1H‐indole‐3‐carboxylic acid). They found that 5F‐PB‐22 was easily detected at 2 × 10 −8 M. Based on a predicted molecular adsorption geometry from the calculated electrostatic potential and the SERS spectrum, it is proposed that the quinoline moiety of the molecule lies in a preponderant parallel orientation to the silver surface with the plane of the indole ring being perpendicular to the surface . Atanasov et al carried out a SERS analyses of thiamethoxam assisted by Ag films and nanostructures that were produced by laser techniques.…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
“…They found that 5F-PB-22 was easily detected at 2 × 10 −8 M. Based on a predicted molecular adsorption geometry from the calculated electrostatic potential and the SERS spectrum, it is proposed that the quinoline moiety of the molecule lies in a preponderant parallel orientation to the silver surface with the plane of the indole ring being perpendicular to the surface. [33] Atanasov et al carried out a SERS analyses of thiamethoxam assisted by Ag films and nanostructures that were produced by laser techniques. Their simple fabrication method and demonstrated efficiency has a direct bearing on human health and food quality by assisting in the detection of small amounts or residue of harmful pollutants.…”
Section: Sers Substratesmentioning
confidence: 99%
“…[11][12][13] In order to get the higher SERS signal enhancement effect, the SERS substrates should have high sensitivity, uniformity, surface purity, good stability, and reproducibility. [14][15][16] Moreover, the SERS signal enhancement of the probe molecules depends on the particle size, particle shape, and interparticle distance of the metal nanoparticles substrates. In general, SERS signal enhancement mainly occurs because of long-range electromagnetic (EM) and short-range charge-transfer (CT) mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…16 Raman and surface-enhanced Raman spectroscopy (SERS) have been reported for the synthetic cannabinoid 5F-PB-22. 17 A DFTsupported in-depth vibrational characterization of JWH-018 in the solid-state and in solution can also be found. 18 Electronic spectra have been calculated for both JWH-250 and JWH-081.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Both the IR and the normal Raman spectra of AMB-FUBINACA and α-PVP have been calculated . Raman and surface-enhanced Raman spectroscopy (SERS) have been reported for the synthetic cannabinoid 5F-PB-22 . A DFT-supported in-depth vibrational characterization of JWH-018 in the solid-state and in solution can also be found .…”
Section: Introductionmentioning
confidence: 99%